Extraction of Genomic DNA from Formalin Fixed - Paraffin Embedded Tissue for Forensic DNA Analysis: Influence of Proteinase K - Maysaa Adil Hadi (Journal of Global Pharma Technology, 2016)
A huge part of tissues preserved throughout the world used in diagnostic aim is formalin-fixed and paraffin embedded tissue (FFPET) which are a highly worthy supply for retrospective (genetic) application contain screening of mutations in cancer-critical genes in addition to detection of pathogens. The purpose of present study was to estimate the best method in the extraction of DNA from FFPET for utilizing in the forensic analysis by comparing three various extraction methods with and without proteinase K digestion and estimated the influence of these procedures of extraction in DNA quality, quantity and polymerase chain reaction (PCR) amplicon. In this study, the comparison was between three DNA extraction methods from five identically processed FFPET. The extraction methods, including DNA extraction kit, phenol: chloroform: isoamyl alcohol with and without proteinase K methods. Amplifiable DNA fragment size was assessed by amplification of exon 7 of CYP1A1 gene and the size of the fragment was (312 bp). Extractions by different methods used in this study were found suitable for amplification of fragment (312 bp) from all tissues used. The best amplification was after extraction without proteinase K and DNA extraction kit. In conclusion, amplification by PCR shows extremely affected by the method of extraction utilized. Pre-treatment of proteinase K was not a prerequisite for extractions of DNA from FFPET and the suitable extraction method was phenol: chloroform: isoamyl alcohol method without proteinase K as it was less time, less cost, yielding a good DNA quantity and quality.Keywords: Formalin Fixed-Paraffin Embedded Tissue, Forensic Analysis, Proteinase K.